PERAN OTORITAS JASA KEUANGAN DALAM MELINDUNGI PEMEGANG POLIS ASURANSI AKIBAT PAILITNYA PERUSAHAAN ASURANSI (Studi Putusan Mahkamah Agung Nomor 408 K/Pdt.Sus-Pailit/2015)Abstract - Muhammad Ridho (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
AbstractThe Financial Services Authority as an institution that oversees activities in the insurance sector functions to create a financial system that grows in a sustainable and stable manner and can foster public confidence in the insurance industry. Within the scope of supervision in the insurance sector, the Financial Services Authority has the authority to submit bankrupt statements to insurance companies in order to protect the interests of insurance policy holders.The purpose of the research in this thesis is to analyze the authority of the Financial Services Authority in the insolvency of insurance companies, to analyze the legal protection of customers who are harmed by the insolvency statement of insurance company to analyze the legal considerations of judges in the Supreme Court’s Decision No. 408 K/ Pdt. Sus-Pailit /2015.The research method used is descriptive analysis that leads to normative juridical research that is research conducted by referring to legal norms that is examining library materials or secondary materials, and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials.The results showed that the Authority of the Financial Services Authority in the insolvency of insurance companies is based on the Bankruptcy Law and Suspension of Debt Payment Obligation (‘UU KKPU’) and Financial Services Authority Act (‘UU OJK’) with its implementation arrangement and the Financial Services Authority’s position as the party submitting an application for bankruptcy statements through the Board of Commissioner of Financial Services Authority. Protection provided to insurance policy holders in the case of bankruptcythat is guaranteed the position of policy holder in the event ofbankruptcy to the insurance company.Judge’s legal consideration in the decision of the Supreme Court Number 408 K/ Pdt. Sus-Pailit /2015 so as to decide on PT. AsuransiJiwaBumiAsih Jaya declared bankrupt is the OJK as a financial service sector supervisory agency authorized to submit bankruptcy requests for insurance companies because PT AsuransiJiwaBumiAsih Jaya is proven to have debt in the form of payment of the policy holder’s claim liability.Key-Words: Role of OJK, Insurance Policy, Bankruptcy.